DETERMINAN NILAI PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE DENGAN PEMODERASIAN KARAKTER EKSEKUTIF - Adi Prayogi, Yoga (Equity: Jurnal Akuntansi, 2024)
This study examines the effect of profitability, liquidity and firm size on firm value with executive character as the moderating variable. The sample in this study is the property and real estate sector companies on the Indonesia Stock Exchange in 2015-2019. Through multiple regression test and absolute difference test, it can be concluded that profitability and firm size do not have a significant effect on firm value, while the liquidity variable has a significant effect on firm value. The executive characteristics variables have not been able to moderate the effect of profitability, liquidity, and firm size on firm value. This indicates that there are other factors besides the executive character, which tend to strengthen performance against company value, such as business value, length of business experience, and other supporting factors.